It's raining pigs & noodles : poems - Prelutsky, Jack.; Stevenson, James, 1929- (New York : Greenwillow Books, 2001)
A collection of humorous poems such as "The Dancing Hippopotami," "You Can't Make Me Eat That," "My Father's Name is Sasquatch," and "Dear Wumbledeedumble."
Includes index.
G12
Keywords: Children's poetry, American; Humorous poetry; American poetry